Implementasi Layanan Konseling Kelompok Dalam Membangun Motivasi Partisipasi Santri Pasca Perubahan Peraturan Di Pondok Pesantren - Rofi'ah, Risatur; Maysaroh, Maysaroh; Milla, Nur Ismatul (At-Taujih : Bimbingan dan Konseling Islam, 2026)
This study aims to analyze the implementation of group counseling services in enhancing students’ participation motivation following regulatory changes in Islamic boarding schools. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving four students and two boarding school administrators. The findings indicate that students’ participation motivation declined due to physical fatigue, changes in activity schedules, and low intrinsic awareness. The implementation of group counseling services was carried out through several stages, namely formation, problem identification, problem-solving, and commitment strengthening. The results show that group counseling has a positive impact on increasing self-awareness, fostering intrinsic motivation, and reducing avoidance behavior. Students gradually demonstrated improved attendance, more cooperative attitudes, and better adaptation to the new regulations. Therefore, group counseling is considered effective in supporting students’ psychological adaptation and enhancing their participation motivation in boarding school activities.   Keywords: group counseling, motivation, participation, students, Islamic boarding school